Importancia de los requisitos específicos de origen como mecanismo impulsor del intercambio comercial de vehículos ensamblados en Venezuela con países Aladi (estudio de casos) (2014)
This article discusses the importance of rules of origin as instruments of trade policy and their impact in the implementation of trade agreements. This research is focused on the application of these rules in the Latin American Integration Association (LAIA), taking into account the automotive sector and how it is developed in the commercial relationship between Venezuela and Colombia, former partner in the Andean Community (CAN) and with Argentina and Brazil, current members of the Southern Common Market (Mercosur). The main objective of this research is to identify the benefits of the application of special requirements of origin for the Venezuelan automotive sector in the context of LAIA between Venezuela and the aforementioned countries. This study is based on the period 2002-2012 as a span in which the most relevant decisions that affects foreign trade of Venezuelan commercial vehicles of different categories with CAN and Mercosur countries were held. This is a descriptive research with a documental design done through revision of commercial agreements, legal texts and bibliography related to the subject of rules of origin. Among the results, it is perceived that Venezuela, despite its productive platform, does not take advantages of rules of origin applied to manufactured vehicles in order to increase regional commercial exchange, since the country quit Andean Community.